1997
DOI: 10.1109/78.552210
|View full text |Cite
|
Sign up to set email alerts
|

Low complexity optimal joint detection for oversaturated multiple access communications

Abstract: Abstract-Optimal joint detection for interfering (nonorthogonal) users in a multiple access communication system has, in general, a computational complexity that is exponential in the number of users. For this reason, optimal joint detection has been thought to be impractical for large numbers of users. A number of suboptimal low-complexity joint detectors have been proposed for direct sequence spread spectrum user waveforms that have properties suitable for mobile cellular and other systems. There are, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 11 publications
(35 reference statements)
0
36
0
Order By: Relevance
“…It is observed that 28% overloading cannot be achieved, with less than 1.0 dB SNR degradation at an average BER of 1e-5. If we reduce the overloading to 25%, the SNR degradation is about 0.35 dB as shown in Figure 3 and we can ensure a BER of 5 …”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that 28% overloading cannot be achieved, with less than 1.0 dB SNR degradation at an average BER of 1e-5. If we reduce the overloading to 25%, the SNR degradation is about 0.35 dB as shown in Figure 3 and we can ensure a BER of 5 …”
Section: Simulation Resultsmentioning
confidence: 99%
“…For example, a method of accommodating K = N + M users in an Ndimensional signal space that does not compromise the minimum Euclidean distance of the orthogonal signaling has been presented in [4] for AWGN channel. A tree-like correlation coefficient structure of user signatures suitable for optimal multiuser detection has been proposed in [5]. In another approach, two sets of orthogonal codes which are orthogonal within the sets is introduced in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Hetling et al [23] have proposed and evaluated the use of wavelet packets as spreading codes in CDMA systems. Learned et al [24] derived an optimal joint detector for the wavelet packet based CDMA communications. The receiver design achieved low complexity detection compared with the conventional CDMA optimal receiver designs.…”
Section: Applications Of Wavelet Packets In Communicationsmentioning
confidence: 99%
“…One obvious approach of using wavelet packets in CDMA communication is using them as signature waveforms, or non-binary spreading codes [23], [24]. In the case of directly using wavelet packets as non-binary spreading codes in a DS-CDMA system, the waveforms are usually chosen from an orthonormal basis such as wavelet packets so that there will be no interference between different users.…”
Section: Wavelet Packets For Doubly Orthogonal Cdma Waveformsmentioning
confidence: 99%
See 1 more Smart Citation